2020
DOI: 10.31254/jmr.2020.6511
|View full text |Cite
|
Sign up to set email alerts
|

A single center experience of Hypospadias Repair in Dar es Salaam, Tanzania

Abstract: Background: Hypospadias is one of the common congenital anomaly that affects children. It can present classically with abnormal ventral opening, chordee and dorsal hood however isolate hypospadias do also exist. Hypospadias repair is one of the commonly performed surgical procedures at Muhimbili National Hospital (MNH) and the outcome of repair is influenced by several factors. Our study aimed to assess the Profile and Early Outcome of Hypospadias repair at Muhimbili National Hospital. Methodology: This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…Interestingly, one descriptive study in Tanzania reported distal hypospadias in general as the commonest type of hypospadias different from the index study; however, their classification was generalized as proximal, mid-shaft, and distal [9]. Nyongole et al reported 33.3% occurrence rate of sub-coronal type among 63 patients with hypospadias at the same settings which nearly the same as in this study [15]. A study in Israel found anterior and mid-shaft hypospadias being the common type among 163 hypospadias patients almost similar to the findings in this study [16].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Interestingly, one descriptive study in Tanzania reported distal hypospadias in general as the commonest type of hypospadias different from the index study; however, their classification was generalized as proximal, mid-shaft, and distal [9]. Nyongole et al reported 33.3% occurrence rate of sub-coronal type among 63 patients with hypospadias at the same settings which nearly the same as in this study [15]. A study in Israel found anterior and mid-shaft hypospadias being the common type among 163 hypospadias patients almost similar to the findings in this study [16].…”
Section: Discussionsupporting
confidence: 67%
“…The finding is slightly lower with Friedman et al with regard to urogenital-associated anomalies that were such anomalies accounted for 20.6% of associated anomalies with undescended testis and micro-penis being the commonest occurring by 3.7% each [16]. Similarly, Nyongole reports undescended testis as the only associated anomaly by 3.2% among patients with hypospadias; however, his study involved 63 patients about two-third of hypospadias patients in this study [15]. Similar findings have been reported in two other different studies at almost the same rate ranges [9,18].…”
Section: Discussioncontrasting
confidence: 64%
“…Our mean operative time of 70 minutes is similar to the reported operative time in the literature using TIP technique. [24][25][26][27][28] We used dorsal fore skin to harvest dartos flap in between suture lines. There is always a learning curve for this technically demanding procedure.…”
Section: Discussionmentioning
confidence: 99%